DOES PERSON-ENVIRONMENT FIT PLAY A ROLE ON APATHY IN LONG-TERM CARE RESIDENTS WITH DEMENTIA?. (11th November 2018) - Jao, Y; Liu, W; Galik, E; Chaudhury, H; Parajuli, J; Holmes, S
Abstract: Approximately 25–84% of nursing home residents with dementia experience apathy. Apathy is characterized by lack of motivation, lack of initiative, decreased responsiveness to environmental stimulation, and a flat mood. Apathy is associated with rapid cognitive decline, poor quality of life, and higher mortality. Lawton's competence and environmental press model suggests that an individual's behavior and affect are influenced by the fit of their functional abilities with the environmental demands. Yet, the relationship between environment and apathy is understudied. Therefore, this study examined the relationship between functional person-environment fit and apathy in dementia. This is a cross-sectional study using the baseline data from two trials of Function Focused Care for residents with moderate to severe cognitive impairment. The sample included 199 residents with dementia recruited from four nursing homes and four assisted living facilities. Functional person-environment fit was measured using the Enabler scale. Apathy was measured using the Apathy Evaluation Scale. Multilevel linear models were used for analysis. Participants were 84 years old on average and the majority were Caucasian female. Findings revealed that greater person-environment fit was associated with lower apathy (β=.017, P=.025). The association was not significant after controlling for age, gender, type of care setting, cognitive function, depression, agitation, and physical function. In conclusion, findings are insufficient to support the association between functional person-environment fit and apathy. Future research may further examine the impact of individual characteristics on the relationship between environment and apathy and explore the impact of social environment on apathy in dementia.